Evaluation Of Students' Critical Thinking Ability In Solving Real Analysis Problems - Reri Seprina Anggraini; Rilla Gina Gunawan; Hedia Rizki (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2025)
Critical thinking skills are essential for students, particularly in solving complex problems in Real Analysis, as these skills foster academic growth and prepare them for professional challenges. However, many students still struggle to apply these skills effectively. Through a qualitative case study involving fifth-semester students from the Tadris Mathematics program, this research explores the students’ critical thinking demonstrate in solving Real Analysis problems, alongside the factors that support or hinder this ability. Data were gathered through semi-structured interviews, observations, and assessments, focusing on students' problem-solving approaches. The results indicate that while most students (62%) exhibit moderate critical thinking skills, a significant portion (38%) face challenges in developing these abilities, with none achieving high-level proficiency. Supporting factors include cognitive ability, motivation, and a conducive learning environment, while barriers include limited understanding of basic concepts, time constraints, and psychological obstacles. Students predominantly relied on procedural methods to solve problems, hindering deeper analytical thinking. The findings highlight the need for more interactive and reflective teaching methods, such as problem-based learning and group discussions, to enhance students’ critical thinking and problem-solving skills. These insights offer valuable recommendations for improving teaching strategies in Real Analysis and contribute to advancing mathematics education in Indonesia.